The Role of NLRP3 Inflammasome in Radiation-Induced Cardiovascular Injury - Huang, Shanshan; Che, Jing; Chu, Qian; Zhang, Peng (Frontiers in Cell and Developmental Biology, 2020)
The increasing risk of long-term adverse effects from radiotherapy on the cardiovascular structure is receiving increasing attention. However, the mechanisms underlying this increased risk remain poorly understood. Recently, the nucleotide-binding domain and leucine-rich-repeat-containing family pyrin 3 (NLRP3) inflammasome was suggested to play a critical role in radiation-induced cardiovascular injury. However, the relationship between ionizing radiation and the NLRP3 inflammasome in acute and chronic inflammation is complex. We reviewed literature detailing pathological changes and molecular mechanisms associated with radiation-induced damage to the cardiovascular structure, with a specific focus on NLRP3 inflammasome-related cardiovascular diseases (CVDs). We also summarized possible therapeutic strategies for the prevention of radiation-induced heart disease (RIHD).